Predictors of medical students' ethical decision-making: A pilot study using the Theory of Interpersonal Behavior. Issue 12 (December 2020) - Li, Honghe; Novack, Dennis H.; Duke, Pamela; Gracely, Edward; Cestone, Christina; Davis, Tiffany
Highlights: The Theory of Interpersonal Behavior is useful in understanding ethical decision-making. Medical students' emotional reaction plays an important role in decision-making. Education in professionalism should aim to enhance students' professional beliefs. Faculty development is critical for positive role modeling of ethical decisions. Abstract: Objective: To understand medical students' (MS) ethical decision-making using the Theory of Interpersonal Behavior (TIB). Methods: We conducted two rounds of focus groups to develop a TIB-based questionnaire by eliciting students' perspectives on an ethical dilemma they will encounter in a standardized patient (SP) station, in which an SP "surgeon" asked them to intubate a sedated patient whom the student knew had requested no student involvement. We administrated questionnaires to 241 third-year MS following this SP station, asking for their decisions in the SP station and if a surgeon made the same request in their clerkship. Confirmatory factor analysis (CFA) was used to test whether observed data fit the proposed TIB-based model. Results: The CFA provided an acceptable fit to the a priori proposed model. Fifty-five percent of students indicated they would intubate in an actual situation versus 18% in the SP station ( p  < 0.05). Using logistic regression, TIB domains affect and facilitating factors reported significant association with students' decisions in both the SP and hypothesized actual situations. Conclusions: The TIB appears to be an effective theoretical framework for explaining students' ethical decision-making. Practice implications: The TIB may guide design and assessment of educational programs for professional formation.